Impact of formation slope and fault on CO2 storage efficiency and containment at the Shenhua CO2 geological storage site in the Ordos Basin, China. (September 2019) - Jing, Jing; Tang, Zhonghua; Yang, Yanlin; Ma, Liangzhe
Highlights: A suite of 3D models with faulting and variable reservoir dip were built based on the Shenhua CCS demonstration site. Plume migration and volumetric storage were found to be a function of reservoir dip and high transmissibility fault zone. The results will help to inform site selection for future CCS projects in the Ordos Basin and other potential storage sites. Abstract: Carbon dioxide (CO2 ) storage security is a key issue in CO2 geological storage (CGS). A three-dimensional (3D) conceptual reservoir model of the Shenhua CO2 geological storage site in the Ordos Basin has been used to investigate the impact of reservoir formation dip and the influence of enhanced permeability fault zones on CO2 storage and migration security. A total of 8 simulations were carried out using the TOUGH2 integral finite difference modelling code with the ECO2N fluid property module. The simulation results showed that the dip of the reservoir formation and fault had a significant impact on CO2 migration and storage security. Increasing the dip of the reservoir increased CO2 migration distance, decreased the total volume of CO2 safely stored in the formation and resulted in increased maximum gas saturation and liquid mass fraction of dissolved CO2 . The presence of fault provided a channel for CO2 leakage and caused an irregular distribution of formation pressure. The onset time of leakage through the fault proved to be a function of formation dip, occurring at 465, 230, and 160 years following commencement of CO2 injection for dips of 5°, 10°, and 15° respectively. The lateral extent of both the high saturation CO2 plume and the plume of dissolved CO2 was greater in the steeply dipping faulted reservoir model, suggesting that gently dipping un-faulted reservoir formations should be selected for future CGS projects in the Ordos Basin.